SUPERIOR SECTOR ANALYSIS IN SOUTH TANGERANG AS DETERMINER OF REGIONAL DEVELOPMENT PRIORITY POLICY - Sutanti, Sutanti; Oktariani, Dwi (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2018)
The important thing for regions that have not been recently established such as South Tangerang City is sustainable economic growth. This study aims to identify and analyze the leading sectors in South Tangerang and to project the South Tangerang City Gross Domestic Product in 2017. The data used in the form of the total value added of goods and services resulting from all the economic activities of South Tangerang City and Banten Province economists based on constant prices in 2000. The analysis method uses the Location Quotient (LQ) model and Shift - Share analysis. Based on the Location Quotion (LQ) method, the base sector is nine sectors, namely (1) the Construction Sector; (2) The sector of large and retail trade, and repair of cars and motorbikes; (3) the sector of providing accommodation and drinking meals; (4) information and communication sector; (5) real estate sector; (6) company service sector; (7) educational services sector; (8) health services sector and social activities; (9) other service sectors. Overall, South Tangerang City has the most superior sector in the real-estate sector. It can be concluded that this sector has a competitive advantage and comparative advantage.